2019
DOI: 10.1051/e3sconf/20198506012
|View full text |Cite
|
Sign up to set email alerts
|

The water footprint from hydroelectricity: a case study for a hydropower plant in Romania

Abstract: In Romania, the hydropower is the main form of renewable source with an important share in energy mix. Despite their valuable advantages on supplying energy and balancing the energy system, public acceptance, environmental, social and economic impact has become a common challenge in development of hydropower projects. Increasing of water consumption and raising awareness regarding available water resources leads to an integrated management approach of them. In this paper the water footprint is estimated for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Besides hydropower generation, more than 40% of the world's reservoirs have multiple purposes, such as irrigation, residential and industrial water supply, flood protection, fishing and recreation, and more [37]. An economic benefit model was used for water consumption allocation in multipurpose reservoirs, and the results showed that hydropower was the major contributor to economic benefits [38]. The orange diamond marker in Figure 5 represents the process-based method at the regional level [34].…”
Section: Comparison Of Water Footprints Of Different Power Typesmentioning
confidence: 99%
“…Besides hydropower generation, more than 40% of the world's reservoirs have multiple purposes, such as irrigation, residential and industrial water supply, flood protection, fishing and recreation, and more [37]. An economic benefit model was used for water consumption allocation in multipurpose reservoirs, and the results showed that hydropower was the major contributor to economic benefits [38]. The orange diamond marker in Figure 5 represents the process-based method at the regional level [34].…”
Section: Comparison Of Water Footprints Of Different Power Typesmentioning
confidence: 99%
“…Robescu a Bondrea [24] spočítaly vodní stopu spojenou s výstavbou hráze vodní elektrárny Vidraru na 19,7 mil. m 3 při objemu hráze 480 000 m 3 , tj.…”
Section: Volumetric Water Footprintunclassified
“…Robescu and Bondrea [24] calculated the water footprint associated with the construction of the dam for the Vidraru HPS to be 19.7 million m 3 , with the dam volume being 480,000 m 3 (i.e., 41 m 3 per m 3 of the concrete dam). Using this information and the volume of Orlík hydraulic structure of about 1.1 million m 3 , the water footprint of Orlík dam is 45.1 million m 3 , or (considering 100 years of service life) 4.51 million m 3 per year.…”
Section: Lca Vodní Stopamentioning
confidence: 99%
“…Mekonnen and Hoekstra 2012 calculate the blue water footprint of 35 taken from selected hydropower plants in a variety of places in the world (representing some 8% of the total installed capacity) concluding that the water evaporation was equivalent to the 10% of the one that corresponds to the global crop production in a year. Other studies show the importance of the water footprint in different locations, such as New Zealand (Herath et al 2011 ) where most of the energy production is generated by hydropower, Romania (Robescu and Bondrea 2019 ) or China (Zhang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%